Crossing borders through folklore : African American women's fiction and art - Billingslea-Brown, Alma Jean, 1946- (University of Missouri Press, 1999)
Examining works by Toni Morrison, Paule Marshall, Faith Ringgold, and Betye Saar, this innovative book frames black women's aesthetic sensibilities across art forms. Investigating the relationship between vernacular folk culture and formal expression, this study establishes how each of the four artists engaged the identity issues of the 1960s and used folklore as a strategy for crossing borders in the works they created during the following two decades. Because of its interdisciplinary approach, this study will appeal to students and scholars in many fields, including African American literature, art history, women's studies, diaspora studies, and cultural studies.